A new species of Leiothrix (Eriocaulaceae) from the Espinhaço Range, Bahia, Brazil - Giulietti, Ana Maria; Silva, Daniele Mendes Da (Phytotaxa, 2016)
A new species of Leiothrix (Eriocaulaceae) from Brazil is described and illustrated. Leiothrix raymondii is a restricted endemic living under the shelter of rocks, in large rocky outcrops, occurring in the Northern part of the Espinhaço range in Bahia state, Brazil. The species is here assessed as endangered.